Language deviation interferential character in the system of modern Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article provides an analysis of the phenomenon of interference, and delineated interferema, superinterferema (components “surzhiks“). Drinking interference level semantic interference dictate the functioning of words with their extrinsic value systems in Russian and Ukrainian languages. Language deviation due to translation errors (use of tracing paper), semantic ambiguity of correlations, lexical significative values constitute deviant components “surzhiks“.
Keywords: interference; interferema; component surzhiks; linguistic norm; codification; semantic modification; linguistic deviation; normativity speech